INFORMAL AND PRECARIOUS: THE CORROSION OF PROTECTION AND RIGHT TO WORK - Reis, Amanda Lima; Giaqueto, Adriana [UNESP] (Fundacao Univ Tocantins, 2020)
The present work seeks to reflect the right to work and its fundamental role in the organization of society, as guaranteed by the Brazilian Federal Constitution of 1988 and the Universal Declaration of Human Rights. In view of the legal achievements in recognition of the right to work as a condition for the maintenance of life and dignity of the human person, the tensions and tendencies contrary to these achievements are placed with the transformations in the contemporary world of work. In this scenario new forms of labor relations guided by informality and precariousness are found, having as a great exponent today the phenomenon of uberization and unrestricted outsourcing, processes characterized by the dissimulation of the relations of subordination between employer and worker and, consequently, diminished access to labor rights. In light of the above, the urgency of rethinking the world of work permeated by informality and precariousness is reaffirmed, as well as the loss of the value of work in the contemporary world.
Keywords: Right to work; Precariousness; Informality; Work in the contemporaneity